A study of A Lecturer’s Teaching Performance in an Online English Academic Writing Course through WhatsApp - Yuniarti Yuniarti; Dwi Rukmini; Januarius Mujiyanto; Sri Wuli Fitriati (International Conference on Science, Education, and Technology, 2021)
In online learning, teaching aspect is important to link students and a lecturer who are not connected physically during Covid19. This study focuses on a lecturer's contribution in teaching academic writing through WhatsApp. Using a case study, the researcher observed the lecturer's performance during teaching online. The researcher garnered data of observation in the form of text-based communication in chatrooms. The researcher analysed observation data using the theory of teaching presence adopted from Garrison and Evans. The researcher took nine indicators of direct instruction and six indicators of facilitating discourse to analyse data. The data analysed used content analysis. The results showed the total contribution to direct instruction was 62,30%. The most frequent teaching performance conducted was the lecturer presented the matter, discussed the topic, and reminded students about learning activities in writing instruction. Meanwhile, the actual contribution to facilitating discourse was 37,69%. The most often action used by an English writing lecturer were setting a climate for learning, encouraging the students' participation, and prompting discussion. Overall, the English writing lecturer gave contributions positively, even though the lecturer could not fully implement the remaining indicators of two types in a teaching-learning process.